Struktur Frasa Verba Bahasa Inggris dan Bahasa Indonesia pada Postingan Instagram @CNN dan @CNNIndonesia (Analisis Teori X-Bar) - Arliva Ristiningrum; Angga Cahyaning Utami; Agus Hari Wibowo (Departement of Mathematics Education, 2023)
Access to news in today's era is increasingly easy and practical with the presence of various social media (medsos) which have transformed into whatever the public wants. In fact, to maintain existence in the market, news that is culturally presented through the print dimension, as well as electronic media has limited access, in its development it can be reached only with the reach of one's hand. CNN news media, for example, utilizes social media by labeling official accounts to transfer information similar to other dimensions, one of which is Instagram, which contains information composed by visual and language constructions in the form of clauses/sentences. The lens of generative linguistics captures this linguistic phenomenon based on X-Bar analysis. This study aims to describe the structure of English and Indonesian verb phrases for Instagram news posts @cnn and @cnnindonesia. The results show that there are differences in the forms of verb phrases from the two languages. Verb phrases in English are more diverse due to the influence of tenses and in Indonesian they function as active and passive sentence markers.